Lecturers’ Readiness and Adoption of Leaning Management System in Nigerian Universities - JIMOH, Taibat B; SHOWUNMI, A. A. (International Journal of Educational Management, 2025)
Information and Communication Technology (ICT) has brought changes in all st human activities in the 21 century and education is not an exception. This has rendered the existing teaching principles and methods unsuitable for the achievement of the educational objectives. In this paper, the researchers examined lecturers’ readiness towards adoption of Learning Management System (LMS) in Universities in South-west Nigeria. The specific objectives of the study were to: (i) examine the readiness of lecturers towards using LMS in universities; (ii) examine the influence of gender, age and ICT skill on lecturers’ readiness to adopt LMS. The population comprised of 6,252 lecturers in the six selected universities. Stratified, proportional and random sampling techniques were used to select 538 lecturers. The research instruments used for the study were validated researcher-designed questionnaire tagged “Lecturers’ Readiness on LMS Adoption Questionnaire” (LRLMSAQ). The reliability coefficient of (LRLMSAQ) were 0.8. Four research hypotheses were tested. The data collected were analyzed using correlation, T-test and ANOVA. The findings of the study were that lecturers’ readiness and adoption of LMS had positive significant (b = 0.539, P < 0.005), also, there was no significant difference in the responses based on gender, age and ICT skills of lecturers on their readiness to use LMS (Male = 4.0261, Female = 4.0278); (Young = 3.97; Old =4.02); and (skilled 3.96; unskilled 4.21) respectively. The study concluded that lecturers’ readiness could guarantee successful adoption of LMS in Nigerian universities.